Causes and Clinical Impact of Loss to Follow-Up in Patients with Proliferative Diabetic Retinopathy. (8th February 2020) - Abdelmotaal, Hazem; Ibrahim, Walid; Sharaf, Mohamed; Abdelazeem, Khaled
Abstract : Purpose . This study determined the clinical impact and causes of loss to follow-up (LTFU) from the patients' perspective in individuals with proliferative diabetic retinopathy (PDR) who received panretinal photocoagulation (PRP) and/or intravitreal injections (IVIs) of antivascular endothelial growth factor (VEGF). Methods . This prospective cohort study included 467 patients with PDR who received PRP and/or IVIs of anti-VEGF between May 2013 and June 2018. LTFU was defined as missing any follow-up visit for any interval exceeding 6 months, provided that patients eventually resumed care. Main outcome measures include rates and causes of LTFU. Results . A total of 391 patients (83.7%) were followed up, and 76 patients (16.3%) were LTFU over the study period. Rates of LTFU decreased with age (P = 0.005 ). Questionnaire analysis conducted for patients' LTFU showed a significant positive correlation between best corrected visual activity (BCVA) loss and patient's lack of trust and satisfaction with treatment (rs = 0.458, P < 0.001 ). There was also a significant positive correlation between treatment unaffordability and number of IVIs of anti-VEGF (rs = 0.55, P < 0.001 ) and lack of social support and age (rs = 0.39, P < 0.001 ). Conclusions . LTFU threatens vision in PDR patients receiving PRP and/or IVIs of anti-VEGF. Possibly, patient-specific LTFU causes should be addressed before treatment in order to minimize the risk of LTFU. The clinical trial is registered with NCT04018326 (trial registration: ClinicalTrials.gov Identifier: NCT04018326, 10th of July 2019 "Retrospectively registered").